2017
DOI: 10.1016/j.cretres.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Cephalopod associations and palaeoecology of the Cretaceous (Barremian–Cenomanian) succession of the Alpstein, northeastern Switzerland

Abstract: The Alpstein (cantons of Appenzell Ausserrhoden, Appenzell Innerrhoden and St. Gallen, northeastern Switzerland) has been of great interest for geologists over the last decades because of its excellent outcrops. However, there was no comprehensive overview over its Cretaceous fossil content. Here, we describe the cephalopod associations, which are moderately to highly diverse in some strata of the Alpstein. Furthermore, we document the regional palaeoecological changes that occurred during the radiation of het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Tajika et al . (2017) showed that Cretaceous cephalopod associations of Switzerland, including heteromorphs (e.g. Emericiceras , Mariella ), are dominant in deep‐subtidal to offshore facies and rare to absent in shallower, carbonate facies.…”
Section: Habitat Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tajika et al . (2017) showed that Cretaceous cephalopod associations of Switzerland, including heteromorphs (e.g. Emericiceras , Mariella ), are dominant in deep‐subtidal to offshore facies and rare to absent in shallower, carbonate facies.…”
Section: Habitat Reconstructionmentioning
confidence: 99%
“…The torticones Turrilitoides and Mariella as well as the hamiticones Anisoceras and Hamites are associated with offshore neritic and oceanic facies. Tajika et al (2017) showed that Cretaceous cephalopod associations of Switzerland, including heteromorphs (e.g. Emericiceras, Mariella), are dominant in deep-subtidal to offshore facies and rare to absent in shallower, carbonate facies.…”
Section: Habitat Reconstruction (1) Taphonomic Controls On Facies mentioning
confidence: 99%
“…In the fossil record, recognition of isolated soft parts of ectocochleate cephalopods is hampered by the scarcity of soft tissue preservation in general. Hence, usually only the hard parts are recognised (e.g., Sharifi et al, 2021;Tajika et al, 2017;Wilmsen & Yazykova, 2003;Wittler et al, 1999). In the case of isolated jaws, it cannot be ruled out that soft parts were present, which then were either eaten by scavengers or were decaying otherwise (Clements et al, 2016).…”
Section: Taphonomical Historymentioning
confidence: 99%
“…The chronostratigraphic range of Eutrephoceras extends from the Upper Jurassic to the Miocene (Kummel, 1956;Landman et al, 2018). Most of the mid-Cretaceous occurrences of this taxon were recorded from European Albian and Cenomanian successions (Ayoub-Hannaa et al, 2018;Jattiot et al, 2021;Kennedy et al, 2008;Machalski & Wilmsen, 2015;Tajika et al, 2017;Wilmsen, 2000Wilmsen, , 2016. The Koppeh Dagh Basin (northeastern Iran), in which the lower Albian to middle Cenomanian sedimentary rocks are exposed as Aitamir Formation, is known for its rich assemblage of diverse macro-and microfossils, but no nautilid fossils have been documented thus far.…”
Section: Introductionmentioning
confidence: 99%